MANAJEMEN PIMPINAN DAERAH MUHAMMADIYAH FAKFAK DALAM MENGEMBANGKAN KUALITAS PENDIDIKAN ISLAM DI KABUPATEN FAKFAK - Baharudin Muhammad Munawi; Surahman Amin; Sukman (Program Studi Manajemen Pendidikan Islam, 2025)
This scientific research aims to analyze management strategies and the influence of leadership management in Muhammadiyah Fakfak on the development of Islamic education quality in Fakfak Regency. The type of research used is descriptive qualitative which is located in the Secretariat of the Muhammadiyah Fakfak Regional Leadership, MI Muhammadiyah Fakfak, MTs Muhammadiyah Fakfak, and MTs Muhammadiyah Tahfizul Quran Fakfak. The primary data source in this study is the Chairperson of the Muhammadiyah Fakfak Regional Leadership, as the main informant and additional informants, namely the Chairperson of the Dikdasmen Council and the Head of the Muhammadiyah Fakfak Madrasah. The data collection methods used are observation, interviews, and documentation. The results of the study indicate that 1) the management strategy of the Muhammadiyah regional leadership in developing the quality of Islamic education is the development of teacher quality, curriculum development, development of educational facilities, and collaboration with 2) the management strategy of PDM Fakfak in developing human resources as educators and managers of Islamic Education Institutions in Fakfak Regency in the form of training and professional development, recruitment and selection, incentive awards, and monitoring evaluations. 3) Analysis of the role of Muhammadiyah Fakfak leadership which can provide implications for the development of the quality of Islamic education including the preparation of a vision and mission through work meetings, curriculum development, training and development, empowerment of educational technology, and management of professional management.